2016
DOI: 10.1016/j.ijfoodmicro.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

LaeA and VeA are involved in growth morphology, asexual development, and mycotoxin production in Alternaria alternata

Abstract: Alternaria alternata is a common filamentous fungus that contaminates various fruits, grains and vegetables causing important economic losses to farmers and the food industry. A. alternata is a mycotoxigenic mould, which may jeopardize human and animal health. Two of the most common A. alternata mycotoxins found in food and feed are alternariol and alternariol monomethyl ether. In this study we examined the role of LaeA and VeA, two regulatory proteins belonging to the velvet family, which have been described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 63 publications
1
43
0
Order By: Relevance
“…Global regulators affect the expression of a wide array of clusters in response to external or internal stimuli in Pezizomycotina. The best‐studied global regulators are transcription factors from the Velvet complex (Sarikaya Bayram et al ., ; Yin & Keller, ; Bayram & Braus, ; López‐Berges et al ., ; Lan et al ., ; Schumacher et al ., ; Estiarte et al ., ; Akhberdi et al ., ). Velvet complex proteins are present across all groups of fungi, but their role in regulating secondary metabolism has barely been studied outside Pezizomycotina (Bayram & Braus, ; Todd et al ., ).…”
Section: Metabolic Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…Global regulators affect the expression of a wide array of clusters in response to external or internal stimuli in Pezizomycotina. The best‐studied global regulators are transcription factors from the Velvet complex (Sarikaya Bayram et al ., ; Yin & Keller, ; Bayram & Braus, ; López‐Berges et al ., ; Lan et al ., ; Schumacher et al ., ; Estiarte et al ., ; Akhberdi et al ., ). Velvet complex proteins are present across all groups of fungi, but their role in regulating secondary metabolism has barely been studied outside Pezizomycotina (Bayram & Braus, ; Todd et al ., ).…”
Section: Metabolic Complexitymentioning
confidence: 99%
“…Velvet complex is also important for sexual development in both Ascomycota and Basidiomycota. External factors include nutrient availability, light, pH or injury, while internal factors refer to specific cell types, senescence or the sexual cycle (Bok & Keller, ; Yin & Keller, ; Brakhage, ; Estiarte et al ., ; Keller, ). These regulators allow the fungus to coordinate the cost‐effective production of secondary metabolites under specific conditions, and in a coordinated manner.…”
Section: Metabolic Complexitymentioning
confidence: 99%
“…In the brown module, CmDTX30 and CmDTX32 were highly upregulated at 24 or 36 h after inoculation, which indicated that some MATE family genes respond to A. alternata infection in the late stage. Alternaria alternata is a filamentous necrotrophic fungus that extracts nutrients from dead cells and produces different host-selective toxins that damage plant tissues 54,55 ; seven pathogenic variants of A. alternata have been identified, which can cause disease in a variety of plants by producing host-specific toxins 2 . Based on the above studies, we speculate that Chrysanthemum leaves may transport toxins out of cells through multidrug resistance proteins, thereby reducing damage.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 26 fungal species isolated, 17 or 65.38% of them were potentially pathogenic to humans. This included Alternaria alternata, which is found in dates and can cause allergies (19) . Onychomycosis is documented to result from Aspergillus sydowii and Ulocladium botrytis (20,21) .…”
Section: Discussionmentioning
confidence: 99%